2013
DOI: 10.1007/s10725-013-9880-x
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic stress stimulates shoot organogenesis in callus of rice (Oryza sativa L.) via auxin signaling and carbohydrate metabolism regulation

Abstract: This study aimed to clarify the possible mechanism of endogenous phytohormone signaling and carbohydrate metabolism during shoot organogenesis induced by osmotic stress in rice (Oryza sativa L. cv. Tainung 71) callus. Non-regenerable calli derived from Tainung 71 immature embryos were inoculated on Murashige and Skoog medium containing 10 lM 2,4-D. They turned to highly regenerable calli (HRC) (regeneration frequency more than 75 %) with lower calli fresh weight and water content when 0.6 M sorbitol was supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 67 publications
3
31
0
Order By: Relevance
“…1, PIN-formed 1, and LEA1 genes in rice callus cultures increased the frequency of shoot regeneration (Lee and Huang, 2014). In this study, increasing the concentration of sucrose to 50 g l −1 in the culture medium significantly decreased the average number of shoots per explant.…”
Section: Adventitious Shoot Regenerationsupporting
confidence: 49%
See 1 more Smart Citation
“…1, PIN-formed 1, and LEA1 genes in rice callus cultures increased the frequency of shoot regeneration (Lee and Huang, 2014). In this study, increasing the concentration of sucrose to 50 g l −1 in the culture medium significantly decreased the average number of shoots per explant.…”
Section: Adventitious Shoot Regenerationsupporting
confidence: 49%
“…This may be due to the osmotic stress resulting from high levels of sucrose in the culture medium (Lee et al, 2002). Osmotic stress stimulates shoot regeneration in callus culture of rice by auxin signaling and regulation of carbohydrate metabolism (Lee and Huang, 2014). The inclusion of high concentration of sucrose to the culture medium may enhance the endogenous level of glucose, fructose, sucrose, starch, auxin, cytokinin, and abscisic acid (ABA) in the explants.…”
Section: Adventitious Shoot Regenerationmentioning
confidence: 99%
“…Auxin stimulates the somatic embryogenesis and plant regeneration on rice callus culture (Vega et al, 2009). Auxin considered as a key factor in somatic embryogenesis which influences osmotic prerequisite and carbohydrate metabolism on shoot regeneration (Lee and Huang, 2014). Huang et al (2012) highlighted that endogenous auxin stimulate shoot regeneration in rice calli.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we reported that HRC contained higher levels of glucose, sucrose, and starch, accomplished with higher mRNA transcription levels of cell-wall bound-invertase 1 (CIN1) and SUTs genes [8,33]. Also, we found that these changes on carbohydrate metabolisms can also be found in osmotic and ABA treated calli, suggesting the possibility of regulation mechanisms on HRC formation [5,11].…”
Section: Introductionmentioning
confidence: 86%
“…Previous studies had identified that added osmotic agents like sorbitol or mannitol in callus induction medium can stimulate HRC formation instead of NRC, thus promoting the shoot formation frequency [5,7,[9][10][11]. It is still unclear why appropriate osmotic stress during callus induction can promote shoot organogenesis frequency, but there were lots of studies indicating that osmotic stress can stimulate endogenous phytohormone abscisic acid (ABA) accumulation which is also proven to have the function of promoting somatic embryogenesis and shoot organogenesis when it used as an exogenous plant growth regulator in callus culture [11][12][13][14][15]. ABA is widely recognized as a negative plant hormone which mainly functions on stress responses and seed dormancy, but when it is treated in low concentration, ABA could become a positive regulator on root elongation [16].…”
Section: Introductionmentioning
confidence: 99%